ANALISIS KOMPETENSI EMOSIONAL GURU PPKN TERHADAP PEMBINAAN KARAKTER SISWA DI SMP NEGERI 3 MEDAN - Siburian, Yeremia Elkana Tua; Pakpahan, Rugun Elis Deoktavia; Stepani, Gabriella (Universitas Methodist Indonesia, 2023)
This study aims to provide the emotional importance of Civics teachers in developing the character of students who tend to be ignored by teachers who educate students with unstable emotions. The method used is descriptive method with a qualitative approach through interviews and observations at SMP Negeri 3 Medan as a data collection tool. From the results of the research conducted, it was found that the teacher's emotionality at SMP Negeri 3 Medan was good as a moral influence and good coaching in developing character.